Dynamics of Collective Memory in Political Rebranding in the Digital Era: Qualitative Content Analysis of “Gemoy” on X in the 2024 Election - Ratna Puspita; Budiharjo, Slamet; Shenthya Winarty (Universitas Telkom, 2024)
This study investigates the usage of the term “gemoy” in the political context, particularly in relation to Prabowo Subianto, and how this term emerged and evolved in conversations on social media platform X, from post-2019 Election to the lead-up to the 2024 Election. Qualitative content analysis method is employed to comprehend the public’s response to the usage of the term “gemoy” as part of Prabowo’s political rebranding, as well as the criticisms that surfaced in the context of society’s collective memory regarding Prabowo’s controversial track record, especially concerning past human rights violations. Findings indicate that while there is a positive response to these rebranding efforts, particularly from Generation Z, criticisms regarding the use of “gemoy” as an attempt to divert attention from more fundamental substantive issues, and resistance to Prabowo’s political rebranding, remain significant, particularly from X users. However, it’s noteworthy that X users do not dominate the population in Indonesia, and the popularity of platform X is influenced by various factors, including its ability to meet its users’ preferences in terms of fast and concise communication. Keywords: political rebranding, collective memory, Prabowo Subianto, 2024 election.